Ryzyko cyklu życia produktu bankowego - Paradecki, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Risk of the banks product life cycle is a consequence of everyone's bank risks. Functioning of the bank is burdened with the: credit risk, risk of the structure of assets and liabilities, market risk and operating risk. The greatest influence on the bank product life cycle has: the credit risk, the risk of the fluidity and the interest rate risk. They are a consequence of the receipt of the product through the market (customers and the competition). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 307-316